1995
DOI: 10.2307/3563639
|View full text |Cite
|
Sign up to set email alerts
|

Who Understands? A Survey of 25 Words or Phrases Commonly Used in Proposed Clinical Research Consent Forms

Abstract: We all write excellent consent forms to be presented to prospective participants in clinical research studies. That is, we think that they are excellent. But many times consent forms are written from our jaded perspective and contain terms of clinical research jargon, common to us, but foreign to a participant. These terms slip through unnoticed because of their familiarity in our everyday language. In a recent study 1 a computer analysis (Flesh-Fry scoring) 2-4 of 71 consent forms at a midwest university show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 7 publications
0
25
0
Order By: Relevance
“…Study participants scored much higher on this question than predicted by previous surveys. Waggoner and Mayo reported that only 75 percent could define the term, 17 but in this survey 81 percent gave a complete definition, and an additional 11 percent had some familiarity with the term placebo. Subjects 41 to 65 years old appeared to have better knowledge than both older and younger groups, with 93 percent writing complete definitions.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Study participants scored much higher on this question than predicted by previous surveys. Waggoner and Mayo reported that only 75 percent could define the term, 17 but in this survey 81 percent gave a complete definition, and an additional 11 percent had some familiarity with the term placebo. Subjects 41 to 65 years old appeared to have better knowledge than both older and younger groups, with 93 percent writing complete definitions.…”
mentioning
confidence: 74%
“…A previous study reported that only 33 percent of respondents to an interview survey knew the term. 17 There was no statistical difference found when knowledge was compared by group, age, or education.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Consent forms do not always use terms that are easily equatable with the experimental nature of the trial (Appelbaum & Lidz, 2008a); common clinical terminology such as efficacy, random, and double-blinded are not typically understood by the lay population, and "treatment" often is used to describe the trial itself (Instone, Mueller, & Gilbert, 2008;Waggoner & Mayo, 1995). Instone et al (2008) noted that therapeutic misconceptions and misestimations can occur within investigators and CTNs.…”
Section: Terminologymentioning
confidence: 98%
“…There is no reason for the IRB committee to spend a lot of time discussing modification to consent forms, which ultimately might be better done by a well-trained specialist. 15 Equally important, we believe that the committee's focus on consent forms takes their attention away from other issues, especially the risks and benefits of the protocol, which are both more difficult to assess and ultimately more important. Leaving consent forms to an IRB staff member will create more time at full board meetings to discuss other difficult and important protocol issues.…”
Section: Leaving the Review Of Consent Forms To The Staffmentioning
confidence: 99%